From basic care to beyond: A Q methodology study into the English communication needs among Thai caregivers of foreign older adults - Athip Thumvichit; Narongdej Phanthaphoommee (Elsevier, 2024)
A shift toward the aging population worldwide brings about a growing demand of caregivers, who can communicate effectively with their care recipients. Using Q methodology, this study investigates the English communication needs among Thai caregivers of foreign older adults, aiming to profile the specific tasks that necessitate effective intercultural communication. Data were collected through card-sorting task and follow-up interviews. The findings show that caregiver's target tasks can be classified into hands-on nurturers, emotional supporters, and trusted companions. The hands-on nurturers focused on tasks requiring direct physical care and day-to-day assistance, emphasizing the role of English in activities such as bathing and aiding with hygiene. The emotional supporters recognized the importance of English in providing psychological and emotional comfort. Trusted companions placed value on English for fostering social connections, engaging in leisurely activities, and facilitating casual exchanges. This study highlights Thai caregivers' multifaceted roles, stressing the necessity for comprehensive English training for intercultural communication in caregiving.